Preparation and application of super-hydrophobic film material

By introducing low surface energy organofluorine silicon and nano-TiO2 onto the surface of polystyrene, micro-nano structures and molecular networks are formed, solving the problem of the lack of durability of superhydrophobic properties in polystyrene films and realizing the durability and self-healing ability of superhydrophobic films.

CN120904499AActive Publication Date: 2025-11-07NANTONG HUANENG NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511449801.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-11
Publication Date
2025-11-07
Estimated Expiration
2045-10-11

AI Technical Summary

Technical Problem

The superhydrophobic properties of existing polystyrene films are not durable and are easily damaged by external forces, leading to the loss of superhydrophobicity.

Method used

Superhydrophobic thin film materials are prepared by introducing low surface energy organofluorine silicon and rough TiO2 onto the surface of polystyrene through chemical copolymerization. KH570 modified nano-titanium dioxide is then copolymerized with organic matter to form micro-nano structures and molecular networks, thereby improving the durability of hydrophobic properties.

Benefits of technology

Even after the surface micro-nano structure of the prepared superhydrophobic thin film material is damaged, the bottom of the coating remains intact, demonstrating self-repair capability and ensuring the durability of the superhydrophobic effect and excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of thin films, and discloses preparation and application of a super-hydrophobic thin film material.The nano TiO2 treated by KH570 is used for forming a certain micro-nano structure on the surface of the material, the specific surface area is increased, cavitation is formed between water drops and the surface of the material, the water drops cannot make contact with the surface of the material, and the super-hydrophobic thin film material is obtained. Meanwhile, dispersion of nanoparticles in a matrix is promoted, the interface bonding strength is improved, and the composite material is endowed with excellent mechanical properties; besides, long-chain alkane with hydrophobic performance is grafted and can be mutually wound and tightly connected with a polystyrene matrix, so that molecular chains generate an intermolecular association effect, a supramolecular network structure is formed, and the hydrophobic performance is further improved; in addition, organic fluorine, silicon and other low-surface-energy substances are introduced to the surface of the material, so that the prepared composite material has low surface free energy, water drops cannot stay on the surface, and the super-hydrophobic effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of thin films, in particular to preparation and application of super-hydrophobic thin film material. BACKGROUND

[0002] The super-hydrophobic material is a kind of bionic functional material based on the "lotus effect", the static contact angle of water droplets on the surface of the material is greater than 150 degrees, and the rolling angle is less than 10 degrees, due to the self-cleaning, waterproof, antifouling, anticorrosion and other characteristics of the super-hydrophobic material, the super-hydrophobic material has a wide application prospect in electrical appliances, chemical industry, national defense and military, etc., polystyrene is a kind of hydrophobic material, and the super-hydrophobic performance of polystyrene can expand its application to a wider range, and in recent years, the polystyrene has become a hot spot in material research.

[0003] There are usually two ways to prepare a super-hydrophobic surface: one is to construct a suitable roughness on the surface of a hydrophobic material; and the other is to modify the surface of a material with suitable roughness with a low-surface-energy chemical substance. The application patent CN115093597A discloses a preparation method of super-hydrophobic polystyrene film, a silica sol is prepared by adopting a sol-gel method, using methyl triethoxysilane as a precursor, tetraethyl orthosilicate as a precursor, anhydrous methanol as a solvent and ammonia water as a catalyst, a nanometer silica gel is prepared, and then a non-solvent induced phase separation principle is used, PS is used as a base material, tetrahydrofuran is used as a good solvent, anhydrous ethanol and the nanometer silica sol are used as non-solvents, and the PS super-hydrophobic film is prepared on a glass substrate by adopting a drop coating method, the obtained super-hydrophobic film has large surface roughness and certain wear resistance, and the preparation process is simple, but the super-hydrophobic performance of the film is derived from the construction of the surface micro-morphology, the PS does not change chemically, and therefore the durability of the super-hydrophobicity is poor, the super-hydrophobicity is easily damaged by external force, and the super-hydrophobicity is lost; the application introduces low-surface-energy organic fluorosilicon and rough TiO2 on the surface of polystyrene by chemical copolymerization, so that the super-hydrophobic performance of the prepared polystyrene film is durable and the process is simple. SUMMARY

[0004] The technical problem solved by the application is to provide preparation and application of super-hydrophobic thin film material, and to solve the problem of poor super-hydrophobic performance of polystyrene thin film material.

[0005] The technical scheme of the application is: The application discloses a preparation method of a super-hydrophobic film material, which is carried out according to the following steps: adding KH570 modified nano-titanium dioxide and toluene solvent into a reaction bottle, stirring uniformly, then adding dibenzoyl peroxide, stirring, adding styrene and bis-difluoromethyl biphenyl dodecene, cooling after polymerization, toluene centrifugal washing, obtaining a super-hydrophobic composite material, then adding the super-hydrophobic composite material into toluene solvent, ultrasonic dispersion, coating a film on a glass substrate by using the obtained dispersion liquid, and obtaining the super-hydrophobic film material after standing and drying.

[0006] Further, the mass ratio of the reactants is as follows: KH570 modified nano-titanium dioxide:dibenzoyl peroxide:styrene: bis-difluoromethyl biphenyl dodecene = (40-64) g:(6-10) g:100 g:(15-40) g.

[0007] Further, the polymerization reaction temperature is 70-90 DEG C, and the reaction time is 5-8 h.

[0008] Further, the preparation method of the bis-difluoromethyl biphenyl dodecene is carried out according to the following steps: (1) adding 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diformyl and dichloromethane solvent into a reaction bottle, stirring uniformly, then adding diethylamine trifluoride, pouring the reaction liquid into ice water after the reaction is completed, adjusting the pH to 8-9 by using saturated sodium bicarbonate solution, standing and separating, dichloromethane extraction of the water phase, organic phase concentration, and column chromatography purification to obtain bis-difluoromethyl biphenyl phenol.

[0009] (2) adding sodium hydride and dimethyl sulfoxide solvent into a reaction bottle, stirring uniformly under nitrogen atmosphere, adding bis-difluoromethyl biphenyl phenol dimethyl sulfoxide solution, stirring at 20-35 DEG C for 1-3 h, then cooling to 0-10 DEG C, adding 12-bromo-1-dodecene, warming reaction, adding deionized water after the reaction is completed, dichloromethane extraction, organic phase concentration, and silica gel column chromatography purification to obtain bis-difluoromethyl biphenyl dodecene.

[0010] Further, the use amount ratio of the reactants and the solvent in the step (1) is as follows: 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diformyl: diethylamine trifluoride:dichloromethane solvent = 1 g:(2.5-3.5) g:(8-10) mL.

[0011] Further, the reaction temperature in the step (1) is 20-35 DEG C, and the reaction time is 2-4 h.

[0012] Further, the amount ratio of each reactant and solvent in the step (2) is: sodium hydride: dimethyl sulfoxide solvent: bis-difluoromethyl diphenol: 12-bromo-1-dodecene = (0.22-0.26) g: (4-8) mL: 1 g: (2.1-2.7) g.

[0013] Further, the reaction temperature in the step (2) is 40-60 DEG C, and the reaction time is 16-24 h.

[0014] Further, the preparation method of the KH570 modified nano titanium dioxide is carried out according to the following steps: adding nano titanium dioxide and ethanol solvent into a reaction bottle, stirring uniformly, adding KH570, adding ammonia water after stirring for 10-30 min, heating to 40-50 DEG C, and reacting for 36-48 h; after the reaction is completed, the ethanol is centrifuged and washed to obtain the KH570 modified nano titanium dioxide.

[0015] The application has the beneficial technical effects that: 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diformaldehyde is subjected to the action of fluorinated reagent diethylamine sulfur trifluoride to obtain bis-difluoromethyl diphenol, then 12-bromo-1-dodecene is subjected to substitution reaction with the phenolic hydroxyl group of bis-difluoromethyl diphenol to obtain bis-difluoromethyl diphenyl dodecene, then KH570 is used to modify the surface of nano TiO2 to obtain modified TiO2 with olefin end groups, and finally the modified TiO2 is copolymerized with bis-difluoromethyl diphenyl dodecene and styrene to form a film to obtain a super-hydrophobic film material.

[0016] The nano TiO2 treated by KH570 can make the organic phase and the inorganic phase composite in the nanometer size range, promote the dispersion of the nano particles in the matrix, improve the interfacial bonding strength, and endow the composite material with excellent mechanical properties; the nano TiO2 can also form a certain micro-nano structure on the material surface, increase the surface area, make the water droplets form "cavitation" on the material surface, and make the water droplets unable to contact the material surface; in addition, the grafting of the long-chain alkane with hydrophobic properties can be closely connected with the polystyrene matrix, make the molecular chains produce intermolecular bonding, form a supramolecular network structure, and further improve the hydrophobic properties; in addition, the introduction of organic fluorine, silicon and other low surface energy substances on the material surface, the bond energy of C-F and Si-O is larger than that of C-H and C-O, and the atomic electron cloud shields the C-C bond more strongly than the H atom, so that the prepared composite material has low surface free energy, can form a very thin molecular layer on the material surface, thereby reducing the surface energy, making the water droplets unable to stay on the surface, and realizing the hydrophobic effect; after the micro-nano structure on the surface of the coating is damaged, the nano structure at the bottom of the coating remains intact, and the new coating can repair the damaged micro-nano structure, ensuring the durability of the super-hydrophobic effect of the composite material. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work fall within the protection scope of the present application.

[0018] The preparation method of the KH570 modified nano-titanium dioxide is performed according to the following steps: 5 g of nano-titanium dioxide and 500 mL of ethanol solvent are added into a reaction bottle, stirred uniformly, 50 mL of KH570 is added, 50 mL of ammonia water is added after stirring for 20 min, the temperature is increased to 40 DEG C, and reaction is performed for 36 h. After the reaction is completed, the ethanol is centrifuged and washed to obtain the KH570 modified nano-titanium dioxide.

[0019] Example 1 (1) 15 g of 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-dicarboxaldehyde and 130 mL of dichloromethane solvent are added into a reaction bottle, stirred uniformly, 45 g of diethylamine trifluoride is added dropwise, reaction is performed at 35 DEG C for 3 h, then the reaction liquid is poured into ice water, saturated sodium bicarbonate solution is used to adjust the pH to 9, and the reaction liquid is left to separate into two layers. The dichloromethane is extracted from the water phase, the organic phase is concentrated, and column chromatography is used for purification to obtain bis-difluoromethyl biphenol.

[0020] (2) 2.2 g of sodium hydride and 60 mL of dimethyl sulfoxide solvent are added into a reaction bottle, stirred uniformly under nitrogen atmosphere, 10 g of bis-difluoromethyl biphenol dimethyl sulfoxide solution is added, stirred at 25 DEG C for 2 h, then the temperature is decreased to 5 DEG C, 23 g of 12-bromo-1-dodecene is added, the temperature is increased to 50 DEG C, and reaction is performed for 18 h. Then deionized water is added, dichloromethane is used for extraction, the organic phases are combined and concentrated, and silica gel column chromatography is used for purification to obtain bis-difluoromethyl biphenyl dodecene.

[0021] (3) 40 g of KH570 modified nano-titanium dioxide and toluene solvent are added into a reaction bottle, stirred uniformly, 8 g of dibenzoyl peroxide is added, stirred, 100 g of styrene and 15 g of bis-difluoromethyl biphenyl dodecene are added, reaction is performed at 85 DEG C for 7 h, then the temperature is cooled, toluene is used for centrifugal washing to obtain a super-hydrophobic composite material. Then the super-hydrophobic composite material is added into toluene solvent, ultrasonic dispersion is performed, the obtained dispersion liquid is coated on a glass substrate to form a film, and the super-hydrophobic film material is obtained after standing and drying.

[0022] Example 2 (1) Into a reaction flask, 8 g of 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-dicarboxaldehyde and 70 mL of dichloromethane solvent were added, stirred uniformly, then 28 g of diethylamine trifluoride was added dropwise, after reaction at 35°C for 4 h, the reaction liquid was poured into ice water, the pH was adjusted to 8.5 with saturated sodium bicarbonate solution, and the liquid was separated after standing, the water phase was extracted with dichloromethane, the organic phase was concentrated, and column chromatography was used for purification to obtain bis-difluoromethyl biphenol.

[0023] (2) Into a reaction flask, 11 g of sodium hydride and 200 mL of dimethyl sulfoxide solvent were added, stirred uniformly under nitrogen atmosphere, then 50 g of bis-difluoromethyl biphenol dimethyl sulfoxide solution was added, stirred at 30°C for 3 h, then cooled to 0°C, 105 g of 12-bromo-1-dodecene was added, and after reaction at 55°C for 20 h, deionized water was added, extracted with dichloromethane, the organic phase was combined and concentrated, and column chromatography was used for purification to obtain bis-difluoromethyl biphenyl dodecene.

[0024] (3) Into a reaction flask, 50 g of KH570 modified nano titanium dioxide and toluene solvent were added, stirred uniformly, then 9 g of dibenzoyl peroxide was added, stirred, 100 g of styrene and 25 g of bis-difluoromethyl biphenyl dodecene were added, and after reaction at 75°C for 6 h, the mixture was cooled and washed with toluene by centrifugation to obtain a super-hydrophobic composite material, then the super-hydrophobic composite material was added to toluene solvent, ultrasonic dispersion was performed, the obtained dispersion liquid was coated on a glass substrate to form a film, and after standing and drying, a super-hydrophobic film material was obtained.

[0025] Example 3 (1) Into a reaction flask, 5 g of 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-dicarboxaldehyde and 45 mL of dichloromethane solvent were added, stirred uniformly, then 17 g of diethylamine trifluoride was added dropwise, and after reaction at 25°C for 3 h, the reaction liquid was poured into ice water, the pH was adjusted to 9 with saturated sodium bicarbonate solution, and the liquid was separated after standing, the water phase was extracted with dichloromethane, the organic phase was concentrated, and column chromatography was used for purification to obtain bis-difluoromethyl biphenol.

[0026] (2) Into a reaction flask, 7.5 g of sodium hydride and 150 mL of dimethyl sulfoxide solvent were added, stirred uniformly under nitrogen atmosphere, then 30 g of bis-difluoromethyl biphenol dimethyl sulfoxide solution was added, stirred at 35°C for 2 h, then cooled to 10°C, 72 g of 12-bromo-1-dodecene was added, and after reaction at 60°C for 22 h, deionized water was added, extracted with dichloromethane, the organic phase was combined and concentrated, and column chromatography was used for purification to obtain bis-difluoromethyl biphenyl dodecene.

[0027] (3) 60 g of KH570 modified nano-titanium dioxide and toluene solvent were added into a reaction bottle, stirred uniformly, 8 g of dibenzoyl peroxide was added, stirred, 100 g of styrene and 35 g of bis-difluoromethyl biphenyl dodecene were added, after reaction at 90°C for 8 h, cooling, toluene was centrifuged and washed, to obtain a super-hydrophobic composite material, then the super-hydrophobic composite material was added into toluene solvent, ultrasonic dispersion, the obtained dispersion liquid was coated on a glass substrate to form a film, after standing and drying, a super-hydrophobic film material was obtained.

[0028] Example 4 (1) 25 g of 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-dicarboxaldehyde and 220 mL of dichloromethane solvent were added into a reaction bottle, stirred uniformly, 70 g of diethylamine sulfur trifluoride was added dropwise, after reaction at 30°C for 3 h, the reaction liquid was poured into ice water, saturated sodium bicarbonate solution was used to adjust pH to 8, standing and separating into layers, dichloromethane was used to extract the aqueous phase, the organic phase was concentrated, column chromatography purification was performed to obtain bis-difluoromethyl biphenyl phenol.

[0029] (2) 5.2 g of sodium hydride and 100 mL of dimethyl sulfoxide solvent were added into a reaction bottle, stirred uniformly under nitrogen atmosphere, 19 g of bis-difluoromethyl biphenyl phenol dimethyl sulfoxide solution was added, stirred at 25°C for 3 h, then cooled to 0°C, 46 g of 12-bromo-1-dodecene was added, after reaction at 60°C for 18 h, deionized water was added, dichloromethane was used for extraction, the organic phases were combined and concentrated, silica gel column chromatography purification was performed to obtain bis-difluoromethyl biphenyl dodecene.

[0030] (3) 64 g of KH570 modified nano-titanium dioxide and toluene solvent were added into a reaction bottle, stirred uniformly, 9.5 g of dibenzoyl peroxide was added, stirred, 100 g of styrene and 40 g of bis-difluoromethyl biphenyl dodecene were added, after reaction at 90°C for 7 h, cooling, toluene was centrifuged and washed, to obtain a super-hydrophobic composite material, then the super-hydrophobic composite material was added into toluene solvent, ultrasonic dispersion, the obtained dispersion liquid was coated on a glass substrate to form a film, after standing and drying, a super-hydrophobic film material was obtained.

[0031] Comparative Example 1 (1) 10 g of 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-dicarboxaldehyde and 90 mL of dichloromethane solvent were added into a reaction bottle, stirred uniformly, 25 g of diethylamine sulfur trifluoride was added dropwise, after reaction at 35°C for 4 h, the reaction liquid was poured into ice water, saturated sodium bicarbonate solution was used to adjust pH to 8, standing and separating into layers, dichloromethane was used to extract the aqueous phase, the organic phase was concentrated, column chromatography purification was performed to obtain bis-difluoromethyl biphenyl phenol.

[0032] (2) Add 2.5 g of sodium hydride and 60 mL of dimethyl sulfoxide solvent into a reaction bottle, stir uniformly under nitrogen atmosphere, add 10 g of bis-difluoromethyl diphenyl phenol dimethyl sulfoxide solution, stir at 25°C for 3 h, then cool to 0°C, add 23 g of 12-bromo-1-dodecene, warm to 60°C for 20 h, then add deionized water, dichloromethane extraction, organic phase is combined and concentrated, silica gel column chromatography purification, to obtain bis-difluoromethyl diphenyl dodecene.

[0033] (3) Add 100 g of styrene and toluene solvent into a reaction bottle, stir uniformly, then add 10 g of dibenzoyl peroxide, stir, add 40 g of bis-difluoromethyl diphenyl dodecene, react at 85°C for 8 h, then cool, toluene centrifugal washing, to obtain hydrophobic composite material, then add hydrophobic composite material into toluene solvent, ultrasonic dispersion, the obtained dispersion is coated on a glass substrate to form a film, and the hydrophobic film material is obtained after standing and drying.

[0034] Comparative Example 2 (1) Add 50 g of KH570 modified nano titanium dioxide and toluene solvent into a reaction bottle, stir uniformly, then add 8 g of dibenzoyl peroxide, stir, add 100 g of styrene, react at 80°C for 6 h, then cool, toluene centrifugal washing, to obtain hydrophobic composite material, then add hydrophobic composite material into toluene solvent, ultrasonic dispersion, the obtained dispersion is coated on a glass substrate to form a film, and the hydrophobic film material is obtained after standing and drying.

[0035] Static contact angle test: a contact angle tester is used to measure the contact angle and rolling angle of water on the film, a microsyringe is used to add droplets to the film, each droplet is 3-5 μL, 5 points are measured for each sample, and the average value is taken.

[0036] Water absorption rate test: the prepared film is immersed in deionized water at 25°C for 24 h at room temperature, the water on the surface of the coating is immediately absorbed with filter paper after taking out, and the mass is accurately weighed, and the average value of three measurements is taken as the result.

[0037] Water absorption rate (%) = (m1-m0) / m0 m0: mass of the film before immersion, m1: mass of the film after immersion.

[0038]

[0039] From the data in the above table, with the increase of the content of modified nano-TiO2 and organic fluorine, the contact angle of the film with water gradually increases, and the rolling angle and water absorption rate decrease. In the comparative example 1 without nano-TiO2, the contact angle of the film is 121.6°, the rolling angle is 12.3°, and the water absorption rate is 8.61%, indicating that the film has certain hydrophobic property. This is because the long-chain alkane with hydrophobic property is closely connected with the substrate, so that the molecular chain produces intermolecular bonding, forms a supramolecular network structure, and improves the hydrophobic property. In the comparative example 2 without organic fluorine, the contact angle of the film with water is 113.8°, the rolling angle is 18.6°, and the water absorption rate is 9.36%, indicating that the hydrophobicity of organic fluorine is good. This is because the surface energy of organic fluorine is low, the bond energy of C-F bond is larger than that of C-H bond, and the atomic electron cloud shielding of C-C bond is stronger than that of H atom. A very thin molecular layer can be formed on the surface of the material, thereby reducing the surface energy and improving the hydrophobicity of the film, but it does not reach the requirement of super-hydrophobic property.

[0040] In examples 1 to 4, both organic fluorine and organic silicon contain nano-TiO2. With the increase of the content of the three, the contact angle gradually increases, the maximum reaches 158.4°, the rolling angle reaches the minimum of 3.6°, and the water absorption rate reaches the minimum of 3.54%. At this time, the super-hydrophobicity of the film is greatly improved. This is because the surface energy of organic fluorine and silicon is low, and the specific surface area of nano-titanium dioxide is large, which can increase the roughness of the film. Therefore, the super-hydrophobicity of the material is very superior because it contains both hydrophobic materials and appropriate roughness. Then, the reason for the decrease of the contact angle and the increase of the water absorption rate is that when the nano-TiO2 is excessive, the agglomeration phenomenon is easy to occur, and the proportion of nano-TiO2 decreases, so that the surface roughness decreases.

[0041] Impact strength test: a combined impact testing machine is used, and a simple beam impact test method is used for testing. The size of the film sample is 50mmx10mmx3mm, the mass of the pendulum is 1J, and the impact speed is 3m / s.

[0042]

[0043] From the above table, the impact strength of the composite material is increased from 2.23kJ / m 2 to 2.99kJ / m 2 , which is higher than that of comparative example 1, indicating that the addition of nano-TiO2 can improve the impact strength of the composite material.

[0044] The above merely describes preferred embodiments of the present application, but is not intended to limit the present application to other forms, and any person skilled in the art can make changes or modifications to the above disclosed technical contents into equivalent embodiments with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiments without departing from the technical solution content of the present application and according to the technical essence of the present application still belongs to the protection scope of the technical solution of the present application.

Claims

1. A method of preparing a superhydrophobic thin film material, characterized by, The preparation method is carried out according to the following steps: adding KH570 modified nano-titanium dioxide and toluene solvent into a reaction bottle, stirring uniformly, then adding dibenzoyl peroxide, stirring, adding styrene and bis-difluoromethyl biphenyl dodecylene, after the polymerization reaction is completed, cooling, toluene centrifugal washing, obtaining the super-hydrophobic composite material, then adding the super-hydrophobic composite material into the toluene solvent, ultrasonic dispersion, obtaining the dispersion liquid, coating into a film on a glass substrate, and obtaining the super-hydrophobic film material after standing and drying.

2. The method of claim 1, wherein the method further comprises: The mass ratio of the reactants is: KH570 modified nano-titanium dioxide:dibenzoyl peroxide:styrene: bis-difluoromethyl biphenyl dodecylene = (40-64) g:(6-10) g:100 g:(15-40) g.

3. The method of claim 1, wherein the method further comprises: The polymerization reaction temperature is 70-90℃, and the reaction time is 5-8h.

4. The method of claim 1, wherein the method further comprises: The preparation method of the bis-difluoromethyl biphenyl dodecylene is carried out according to the following steps: (1) adding 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diformyl and dichloromethane solvent into a reaction bottle, stirring uniformly, then adding diethylamine trifluoride, after the reaction is completed, pouring the reaction liquid into ice water, adjusting the pH to 8-9 with saturated sodium bicarbonate solution, standing and separating, dichloromethane extracting the aqueous phase, concentrating the organic phase, and purifying by column chromatography to obtain bis-difluoromethyl biphenyl; (2) adding sodium hydride and dimethyl sulfoxide solvent into a reaction bottle, stirring uniformly under nitrogen atmosphere, adding bis-difluoromethyl biphenyl dimethyl sulfoxide solution, stirring at 20-35℃ for 1-3h, then cooling to 0-10℃, adding 12-bromo-1-dodecene, and warming to react, after the reaction is completed, adding deionized water, dichloromethane extraction, combining the organic phase and concentrating, and purifying by silica gel column chromatography to obtain bis-difluoromethyl biphenyl dodecylene.

5. The method of claim 4, wherein the method further comprises: The use amount ratio of the reactants and solvent in step (1) is: 4,4'-dihydroxy-[1,1'-biphenyl]-3,3'-diformyl: diethylamine trifluoride:dichloromethane solvent = 1g:(2.5-3.5)g:(8-10)mL.

6. The method of claim 4, wherein the method further comprises: The reaction temperature in step (1) is 20-35℃, and the reaction time is 2-4h.

7. The method of claim 4, wherein the method further comprises, The use amount ratio of the reactants and solvent in step (2) is: sodium hydride: dimethyl sulfoxide solvent: bis-difluoromethyl biphenyl: 12-bromo-1-dodecene = (0.22-0.26)g:(4-8)mL:1g:(2.1-2.7)g.

8. The method of claim 4, wherein the method further comprises, The reaction temperature in step (2) is 40-60℃, and the reaction time is 16-24h.

9. The method of claim 1, wherein the method further comprises, The preparation method of the KH570 modified nano-titanium dioxide is carried out according to the following steps: adding nano-titanium dioxide and ethanol solvent into a reaction bottle, stirring uniformly, adding KH570, stirring for 10-30min, then adding ammonia water, warming to 40-50℃ for 36-48h, after the reaction is completed, ethanol centrifugal washing, and obtaining the KH570 modified nano-titanium dioxide.

Citation Information

Patent Citations

  • Preparation method of super-hydrophobic polystyrene film

    CN115093597A

  • Ultrahydrophobic polypropylene / titanium dioxide composite film and preparation method thereof

    CN102675728A

  • Titanium dioxide / polystyrene core / shell particle composite material and preparation method thereof

    CN106749790A

  • Double-fluorine-containing-group-substituted bis(difluoromethoxy) bridged biphenyl liquid crystal compound as well as preparation method and application thereof

    CN111286343A

  • Synthesis method of 4-difluoromethoxy-1-difluoromethyl-2-fluorobenzene

    CN119059887A